2011
DOI: 10.1021/jp207876k
|View full text |Cite
|
Sign up to set email alerts
|

Protein Dynamics and Enzymatic Chemical Barrier Passage

Abstract: After many decades of investigation, the manner in which enzymes increase the rate of chemical reactions, at times by a factor of 1017 compared to the rate of the corresponding solution phase reaction, is still opaque. A topic of significant discussion in the literature of the past 5–10 years has been the importance of protein dynamics in this process. This feature article will discuss the authors' work on this still controversial topic with focus on both methodology and application to real systems. The end co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 78 publications
0
85
0
Order By: Relevance
“…Computations by Miller and coworkers (62) on dihydrofolate reductase (DHFR) indicate highly localized nonstatistical heavy-atom dynamics that are restricted to the atoms of the H-donor and -acceptor. Schwartz and coworkers (6365) are among the few that invoke an extended network of nonstatistical dynamics, specifically for lactate dehydrogenase and purine nucleoside phosphorylase. A recent experimental test of the latter involved the preparation of protein labeled with 13 C, 15 N, and 2 H followed by comparison of its catalytic behavior with that of the native protein (66).…”
Section: Protein Dynamics Linked To Hydrogen Tunneling Efficiencymentioning
confidence: 99%
“…Computations by Miller and coworkers (62) on dihydrofolate reductase (DHFR) indicate highly localized nonstatistical heavy-atom dynamics that are restricted to the atoms of the H-donor and -acceptor. Schwartz and coworkers (6365) are among the few that invoke an extended network of nonstatistical dynamics, specifically for lactate dehydrogenase and purine nucleoside phosphorylase. A recent experimental test of the latter involved the preparation of protein labeled with 13 C, 15 N, and 2 H followed by comparison of its catalytic behavior with that of the native protein (66).…”
Section: Protein Dynamics Linked To Hydrogen Tunneling Efficiencymentioning
confidence: 99%
“…Each protein substate is characterized by a unique rate constant for the chemical conversion step(s), with the most rapid rates occurring when the alignment of active site residues in relation to substrate(s) provides a precise tuning of electrostatic potentials and internuclear distances. 17 While computational studies have proposed a direct coupling of protein motions to the chemical step(s), 53 more experimental data are needed to support such a view. Thus far, the motions that influence catalysis are assumed to be sampled in a statistical manner that precedes the bond cleavage process.…”
Section: Detecting the Role Of Conformational Landscapes In The C–h Bmentioning
confidence: 99%
“…Computational studies have suggested that fast protein motions or promoting vibrations 14 are involved in the chemical step, where covalent bond breaking or formation takes place. 15-20 To test this hypothesis, isotopically labeled “heavy enzymes” were employed by Schramm and co-workers, followed by several other researchers. 14,21-31 In those studies the protein was uniformly labeled with 13 C, 15 N and/or 2 H at non-exchangeable positions to cause vibrational perturbations.…”
Section: Introductionmentioning
confidence: 99%